Ambiguitas Pengaturan Subsidi Teknologi Tinggi Dalam WTO: Studi Kasus Sengketa Airbus Vs Boeing - Rochella Amalia Narindra (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The Airbus–Boeing dispute is one of the most complex cases in WTO history and serves as a clear example of how the subsidy rules in the Agreement on Subsidies and Countervailing Measures (SCM Agreement) are not fully capable of regulating subsidy practices in high-tech industries. This study examines how the European Union government's support for Airbus and the United States' support for Boeing have led to differing interpretations in determining whether a subsidy violates WTO provisions. Using a normative juridical approach, this study analyzes the provisions of the SCM Agreement, the panel and Appellate Body decisions in the DS316 and DS353 disputes, and academic perspectives on legal uncertainty in subsidy regulation. The results show that concepts such as specificity, benefit, and proof of causality remain significantly ambiguous when applied to industries with high research costs and long-term funding structures. The Airbus–Boeing dispute underscores the need to update WTO subsidy rules to be more responsive to the needs of modern technology industries and to provide legal certainty in global competition.